Distribution of Dental Diseases and Treatment Delivered amongst Patients Visiting Dental Outpatient Department at Gandaki Medical College, Nepal - Tuladhar, S L; Parajuli, U; Manandhar, P; Subedi, N; Kunwar, D (Journal of Gandaki Medical College-Nepal, 2018)
Introduction: A study of dental diseases amongst patients attending dental outpatient department (OPD) helps us plan a preventive, and/or a definitive dental treatment.Objectives: To find out the distribution of dental diseases amongst patients visiting dental OPD at College of Dental Surgery, Gandaki Medical College (GMC), Pokhara, Nepal.Methods: The present study was a hospital based cross sectional descriptive study carried out during a period of one year extending from 1st February 2016 to 31st January 2017. A total of 3052 patients attending the dental OPD were included in the study. The distribution of dental diseases according to sex, age and diagnosis were collected and analyzed. Additionally, frequency distribution of treatments provided to the patients was observed.Results: Dental caries was the most prevalent dental disease (64.41%) followed by gingivitis (13.04%). The prevalence of dental caries was significantly higher in females (Females 56.91% vs. males 43.08%, P